Monitoring Indian “Superfood” Moringa oleifera Lam. – species-specific PCR-fingerprint-based authentication for more consumer safety - Sascha Wetters; Vaidurya Sahi; Lena Brosche; Annette Häser; Peter Nick (npj Science of Food, 2024)
Abstract Moringa oleifera Lam. has become one of the major new superfoods commonly available in the aisles of bio-shops and health-food sections in supermarkets of North America and Europe. While most of these products appear under the generic and scientifically inconclusive term “Moringa”, the European Union, so far, has allowed commercialisation for the use in food and feed for M. oleifera only. M. oleifera is indigenous to India and South Asia, but large-scale cultivation of this species has spread to the tropical regions on all continents, with a strong focus on Africa, leading to a high risk of admixture with species like M. stenopetala (Baker f.) Cufod. that is native to Africa. In the present study, we have characterised six species of Moringa in order to develop a simple and robust authentication method for commercial products. While the plants can be discriminated based on the pinnation of the leaves, this does not work for processed samples. As alternative, we use the plastidic markers psbA-trnH igs and ycf1b to discern different species of Moringa and develop a diagnostic duplex-PCR that clearly differentiates M. oleifera from other Moringa species. This DNA-based diagnostic assay that does not rely on sequencing was validated with commercial products of “Moringa” (including teas, powders, or capsules). Our method provides a robust assay to detect adulterations, which are economically profitable for costly superfood products such as “Moringa”.